2012
DOI: 10.4209/aaqr.2011.11.0214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Negative Air Ions on Fog and Smoke

Abstract: A negative electric discharge voltage generator (NAI Generator) was designed and used to investigate the possibility of reducing (neutralizing) fog, dhoop smoke, and vehicle smoke collected in closed glass containers. The experiment was carried out in a dark room, and two identical glass containers were used. Various sensitivity tests were carried out with fog and smoke. Light intensity was measured for each run as a function of time with and without a negative air ion generator. Negative air ions attach to pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 31 publications
1
26
0
3
Order By: Relevance
“…in the air as well as on the inanimate surfaces was also reported in that study. Other successful applications of air ionizers have also been reported for particle control in closed environment (Shiue et al, 2011;Sawant et al, 2012). In this study, though the efficient air ventilation that homogenize the air quality in the ICU may explain the lack of noticeable microbial concentration differences on the two sides of the air purifiers, one may still argue that the local air purifiers do not work well in open-space ICU.…”
Section: Effects Of Patient Visitation Activities and Local Air Purifmentioning
confidence: 48%
“…in the air as well as on the inanimate surfaces was also reported in that study. Other successful applications of air ionizers have also been reported for particle control in closed environment (Shiue et al, 2011;Sawant et al, 2012). In this study, though the efficient air ventilation that homogenize the air quality in the ICU may explain the lack of noticeable microbial concentration differences on the two sides of the air purifiers, one may still argue that the local air purifiers do not work well in open-space ICU.…”
Section: Effects Of Patient Visitation Activities and Local Air Purifmentioning
confidence: 48%
“…PM concentration was reduced by up to two orders of magnitude after 2 hours of treatment by NAI generator in an unoccupied office room (50 m 3 ) [ 144 ]. Many other similar reports showed the high efficiency of NAIs in PM removal ( Table 3 ; [ 138 , 140 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 ]). Evidence showed that many factors might affect PM reducing efficiency by NAIs ( Table 3 ; [ 34 , 139 , 150 , 153 ]).…”
Section: The Release Of Negative Air Ions As An Efficient Way To Rmentioning
confidence: 72%
“…Under similar conditions of the electric circuit the loss of the positive corona is greater than that of the negative corona at the same applied voltage. Because the negative corona curve is flatter and since larger negative corona currents can be obtained, the negative corona is much better adapted for applications such as fog elimination and electrical precipitation than the positive corona (Sawant et al, 2012;Strong, 1913) The wire electrode is a low-cost and high-efficiency plasma source configuration, especially for the large-scale corona discharge system. For a wire electrode radius within the range of 100 to 1000 µm, the plasma thickness increases with increasing wire radius.…”
Section: Corona Discharge Installation and Ion Measurementsmentioning
confidence: 99%